Accommodating Asylum Seekers and Refugees in Indonesia: From Immigration Detention to Containment in “Alternatives to Detention” - Missbach, Antje (Refuge: Canada’s Journal on Refugees, 2017)
Considered the last ‘stepping stone’ before Australia, Indonesia plays an important role in immobilising secondary movements of asylum seekers and refugees in Southeast Asia. While migration scholarship has dedicated substantial attention to immigration detention and the deplorable living conditions inside immigration detention centres (IDCs), this article explores “alternatives to detention” (ATD) in two Indonesian localities: the city of Makassar and the province of Aceh. Seeking to contribute to a critical examination of ATD more generally, this article examines individual freedom, mobility, mechanisms of care and aid provision, protection of rights, self-determination, and matters of personal safety. The article illustrates the remaining limitations and the lack of rights that asylum seekers and refugees in Indonesia continue to face outside of IDCs. A durable solution, in the form of integration, is not available to asylum seekers and refugees, as they are prevented from integrating into the local host societies, and their social and economic mobility remains widely restricted. Yet at the same time, despite more physical mobility in ATD, asylum seekers and refugees remain contained within Indonesia as their onward movement remains deterred as well.